New Routes to Troponoid Natural Products - Wells, Jason Matthew (Curtin University, 2018)
Tropolones have antimalarial activity with a structure unique compared to current treatments. This study focuses on the development of new methods to prepare tropolones and devise a total synthesis of cordytropolone. A new synthesis of tropolones has been developed using thiophene-1,1-dioxides which are a versatile group of compounds that, to date, have been underutilised in organic synthesis. Substituted thiophene-1,1-dioxides can undergo Diels-Alder reactions with cyclopropenes to form cycloheptatrienes which can be converted to tropolone derivatives.